Land Topography Measurement of the Ibnu Al-Mubarok Islamic Boarding School, Rumbai District, Pekanbaru City - Fadrizal Lubis; Widya Apriani; Hendri Rahmat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Ibnu Al Mubarok Islamic Boarding School is an Islamic Education Institution under the Ulil Albab Al Ja'afariyah foundation located on Jl. Sri Palas, Rumbai Bukit, Rumbai District, Pekanbaru City, in its construction activities the Islamic Boarding School requires a topographic map as a basis for planning the Site Plant so that the location of the building can be arranged properly. The method used in solving in the field by conducting a topographic measurement survey of the tool used is the Total Station (TS). The results of topographic measurements show that in the Islamic boarding school area with an area of ± 40,227.8 m² or 4,23 Ha the condition of the land is quite high with an elevation interval of 0 m – 6,534 m and there is an area of development of the Islamic boarding school covering an area of 8453.68 m² or 0,84 Ha, in almost flat soil conditions couded between 0 m – 1,887 m